2013
DOI: 10.1097/imi.0b013e31828d5f15
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracic Surgery Lobectomy versus Lobectomy by Thoracotomy for Lung Cancer: Pilot Study

Abstract: Objective Video-assisted thoracic surgery lobectomy (VATS-L) has become accepted as a safe and effective procedure to treat early-stage non–small cell lung carcinoma (NSCLC). However, the advantages of VATS-L compared with lobectomy by thoracotomy (TL) remain controversial. The aim of this study was to compare the outcomes of patients who underwent VATS-L with those who underwent TL. Methods We studied 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Patients operated by VATS were older, and had a lower cancer stage, slightly lower Charlson comorbidity score, smaller tumours and a higher frequency of adenocarcinoma. These findings are in accordance with several studies [9,15,19,20]; however, confounding by indication cannot be disregarded due to these differences. The multi-institutionaland the national studies by Philips et al and Paul et al, respectively, did not include cancer stage [14,15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Patients operated by VATS were older, and had a lower cancer stage, slightly lower Charlson comorbidity score, smaller tumours and a higher frequency of adenocarcinoma. These findings are in accordance with several studies [9,15,19,20]; however, confounding by indication cannot be disregarded due to these differences. The multi-institutionaland the national studies by Philips et al and Paul et al, respectively, did not include cancer stage [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…In this large study, we found that patients operated by VATS had significantly lower prevalence of both minor and major complications, which included atrial fibrillation, pneumonia, renal failure, sepsis, costa fracture and need for intensive care unit, even after adjustment for other risk factors. Similar findings were reported in other studies [9,[14][15][16][17]. Our multivariate analysis showed that the surgery method had larger impact on the prevalence of complications than gender, age, cancer stage, comorbidity, year of surgery and FEV1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to evidence-based medicine, there is no significant difference between curative effect of thoracoscopic lobectomy and thoracotomy lobectomy for stage I NSCLC. [6,[11][12][13][20][21][22] However, adopting VATS or thoracotomy for the treatment of early stage lung cancer has been controversial, and conflicting evidence exists in the form of large retrospective studies that failed to show any significant benefit from VATS. [23] Its adoption has been variable, likely due to perceived technical challenges when compared to an open approach and a concern for intraoperative complications, especially whether VATS is radical or not.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Many published studies had demonstrated encouraging outcomes of this procedure when compared with conventional thoracotomy, including reduced incidence of arrhythmias, pneumonia, pain and lower levels of inflammatory markers, shorter length of hospital stay, milder pain, less intraoperative blood loss, more rapid return to normal activities, earlier ability to receive adjuvant therapy, and higher postoperative quality of life. [8][9][10][11][12][13][14] In 2006, minimally invasive surgical treatment of lung cancer was written in NSCLC clinical practice guidelines of National Comprehensive Cancer Network (NCCN). [15] The 2013 version of the NCCN guidelines recommended that VATS is a reasonable and acceptable approach for patients with no anatomic or surgical contraindications, as long as there is no compromise of standard oncologic dissection principles of thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%